Nursing of a patient with allergic rhinitis- induced nasal congestion treated by Huolong cupping therapy combined moxibustion (火龙罐综合灸治疗过敏性鼻炎鼻塞症状1例的护理体会) - YANG Yuanyuan (杨媛媛) (Association of Integrative Nursing, 2024)
This paper summarized the nursing of a patient with allergic rhinitis-induced nasal congestion treated by Huolong cupping therapy combined moxibustion. Based on the syndrome differentiation and principals of Traditional Chiense Medicine, the Huolong cupping therapy combined moxibustion was carried out to regulate psychical constitution, activate immune system function and relieve the clinical symptoms of allergic rhinitis-induced nasal congestion. (本文总结火龙罐综合灸治疗1例过敏性鼻炎患者鼻塞症状的护理经验。根据患者的辨证分型, 明确中医治则, 在常规干预的基础上采用火龙罐综合灸调节神经机能, 挟正去邪, 补益强身, 激活免疫系统功能, 提高患者抗过敏能力, 从而有效改善过敏性鼻炎鼻塞症状。)